IMPLEMENTASI PERDA NO. 6 TAHUN 2003 TENTANG PANDAI BACA TULIS AL-QUR’AN BAGI PESERTA DIDIK SEKOLAH DASAR DAN MADRASAH IBTIDAIYAH DI KELURAHAN PULAI KOTO TANGAH KOTA PADANG - Reski Fauji; Ahmad Lahmi; Mursal Mursal (Tarbiyah al-Awlad, 2021)
This study aims to analyze the implementation of the regional regulations of the city of Padang which oblige SD / MI students to be proficient in reading the Qur'anic tilis. This research is a descriptive study using qualitative methods. The informants in this study were the Head of the Koto Pulai BKS, the Head and Teacher of the TPQ, the student guardians and students. The research data were collected by means of interviews, observation and documentation. The results of the analysis show that: 1). This regional regulation has not been implemented properly. This is due to the lack of socialization to the community and the lack of attention from related parties, so that this regulation is allowed to run without proper evaluation and supervision. 2). Efforts made in the process of implementing this regional regulation are: increasing teacher competence by carrying out training every year, emphasizing publishing a curriculum and finding good methods in the learning process. 3) Supporting and inhibiting factors, namely: teaching staff, parents' support and motivation, incentive assistance from the government, lack of support from related parties.